Phonological Variation in Rural Jamaican Schools. - Lacoste, Véronique (Creole language library., 2012)
This book investigates variation in the classroom speech of 7-year-old children who are learning Standard Jamaican English as a second language variety in rural Jamaica. For sociolinguists and second language/dialect researchers interested in the acquisition and use of sociolinguistic variables, an important challenge is how to efficiently account for language learning mechanisms and use. To date, this book is the first to offer an interdisciplinary look into phonological and phonetic variation observed in primary school in Jamaica, that is from the perspective of classic variationist and quan.